Pelatihan Pembuatan dan Pengamatan Preparat Sel Jamur di SMA Negeri 1 Banawa - Slamet Ifandi; Astri Febriana Iffaf; Hermin Lastri Gintoe (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This community service activity focuses on training in the preparation and observation of fungal cell preparations at SMA Negeri 1 Banawa, Donggala Regency. The issue faced is the lack of understanding and skills among students in the field of biology, particularly regarding the structure and function of fungal cells. The goal of this activity is to enhance students' understanding of basic biological concepts and practical skills in preparing fungal cell preparations. The methods used in the training include opening, introducing basic theory, preparing preparations, and microscopic observation. The research results indicate that students successfully prepared samples from spoiled ketan rice, moldy bread, and spoiled tempeh. Microscopic observations allowed students to identify the morphology and structure of fungal cells well, as well as increase their interest in biological sciences. This activity demonstrates significant potential in enhancing scientific literacy and environmental awareness among students.